2011
DOI: 10.30843/nzpp.2011.64.5981
|View full text |Cite
|
Sign up to set email alerts
|

Control of powdery mildew (<i>Sphaerotheca pannosa</i> var <i>rosae</i>) on rose (<i>Rosa</i> L sp) using anhydrous milk fat and soybean oil emulsions

Abstract: Powdery mildew (PM) is a serious fungal disease of a wide range of horticultural crops and can adversely affect crop yield and quality Anhydrous milk fat (AMF) and soybean oil (SBO) emulsions were evaluated for control of PM (Sphaerotheca pannosa var rosae) on potted rose plants (Rosa L sp Splendid Surprise and Sahara) maintained in a controlled environment Foliage was sprayed weekly with AMF (07 w/v) SBO (2 w/v) fungicide (Supershield 1 v/v) water or left unsprayed PM infection increased to 100 leaf area in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Anhydrous milk fat (AMF) and soybean oil (SBO) emulsions were evaluated for control of PM (S. pannosa var. rosae) on potted rose plants maintained in a controlled environment (Chee et al, 2011). Foliage was sprayed weekly with AMF (0.7% w/v), SBO (2% w/v).…”
Section: Resultsmentioning
confidence: 99%
“…Anhydrous milk fat (AMF) and soybean oil (SBO) emulsions were evaluated for control of PM (S. pannosa var. rosae) on potted rose plants maintained in a controlled environment (Chee et al, 2011). Foliage was sprayed weekly with AMF (0.7% w/v), SBO (2% w/v).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding cow milk, it has been studied by many researchers (Bettiol, 1999;Chee et al, 2011;, Choudhary et al, 2018Crisp, 2006;DeBacco, 2011;Ferrandino and Smith, 2007;Guzmán-Plazola et al, 2011;Keinath and DuBose, 2012;McMillan and Vendrame, 2006;Nam et al, 2005;Shah, 2000). Most of the plant protection activity is due to its antifungal properties (Mudgil et al, 2022;Kumar and Kumar, 2021;Sudisha et al, 2011;Wurms and Chee, 2011).…”
Section: Cow Milkmentioning
confidence: 99%
“…Disease control offered by mineral oils, along with oils derived from plants and animals, is also very durable [19,20]. Research to date has shown that NP1 and NP2 were highly effective against various PM pathogens on different crops in laboratory and glasshouse experiments [21][22][23][24][25]. However, these environments were artificially controlled, and product efficacy in a highly variable field environment was unknown, hence the need for the current research.…”
Section: Introductionmentioning
confidence: 99%